Privatization and Restructuring in Concentrated Markets - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2003)
This paper examines the restructuring of state assets in markets deregulated by privatizations and investment liberalizations. We show that the government has a stronger incentive to restructure than the buyer: A firm restructuring only takes into account how much its own profit will increase. The government internalizes that restructuring increases the sales price not only from the increase in the acquirer's profit, but also from a reduced profit for the non-acquirer, whose profits decrease due to its rival's restructuring. We also identify situations where a slow sale can significantly reduce the sales price because of strategic investment and product market effects.
Keywords: D44; L10; L33; L40; P31; 330; Privatization; Asset Ownership; Restructuring; Privatisierung; Oligopol; Unternehmenskonzentration